The perception of municipal managers on the management of urban solid waste - Dall’Agnol, Ana Luiza Bertani; Loebens, Larissa; Demarco, Carolina Faccio; Araujo, Mélory Maria Fernandes de; Leandro, Diuliana; Castro, Andréa Souza; Quadro, Maurizio Silveira (Ciência e Natura, 2019)
The solid waste management in Brazil is supported by the National Solid Waste Policy (PNRS) and, in the case of municipal waste, the responsibility lies for municipalities. The aim of this research was to describe the perception of the managers of the municipalities of the South Region of Rio Grande do Sul regarding solid waste management. Through the application of a questionnaire addressed to the managers of the cities, difficulties were identified: the lack of technical and financial resources for the implementation of the instruments proposed by the PNRS, such as the Municipal Integrated Solid Waste Management Plans (PMGIRS) and selective collection of municipal solid waste. In addition, there were found problems as the lack of collaboration of the population for the functioning of collection systems and difficulties in the insertion of cooperatives and associations of collectors of recyclable materials within the management cycle. Despite the problems faced, managers recognize the importance of integrated solid waste management to improve management and planning of actions, to promote environmental quality and public health and as a method to reduce costs and raise funds.